A non-essentialist view of temporality: Theorizing international students' experiences as forms of future-oriented waiting - Zhao, Xian (Journal of International Students, 2026)
Time is a pervasive dimension of international students’ experiences. However, little research has examined international students’ temporal experiences, particularly how time elicits affective responses. This article addresses this gap by adopting a non-essentialist view of time. Through narrative interviews with four Chinese postgraduate students in the UK, I find that they experienced temporal oppression due to the compressed, accelerated program. They often stayed up late to make time for their academic assignments. However, students reclaimed their temporal agency when they used a prospective perspective (imagining looking back on the present from the future), and they then viewed the accelerated one-year programme as valuable and precious. By theorizing international students’ experiences as future-oriented waiting, this study explores the affective dimension of temporality in their everyday lives and provides empirical insights into students’ lived temporal experiences.